Vitamin D levels of pregnant immigrant women and developmental disorders of language, learning and coordination in offspring - Arrhenius, Bianca (Public Library of Science, 2025)
Background
Prenatal vitamin D deficiency is a common health concern among immigrants. No previous studies have examined the associations between prenatal vitamin D levels and developmental disorders of language, scholastic skills, and coordination in an immigrant sample.
Methods
The sample included 542 immigrant mothers of cases with language, scholastic, coordination or mixed developmental disorders, 443 immigrant mothers of controls without these disorders and 542 Finnish mothers of controls. Maternal vitamin D was measured in serum samples collected during early pregnancy and stored in a national biobank.
Results
The mean vitamin D levels during pregnancy were 25.0 (SD 14.4) nmol/L for immigrant mothers of cases, 25.4 (SD 15.5) for immigrant mothers of controls and 42.3 (SD 19.1) for Finnish mothers of controls. Low maternal vitamin D levels during pregnancy were not associated with the selected developmental disorders in offspring when immigrant mothers of cases were compared to immigrant mothers of controls (adjusted OR for continuous log-transformed vitamin D: 1.01, 95% CI 0.75–1.36, p = 0.96). When immigrant mothers of cases were compared to Finnish mothers of controls, the adjusted OR for continuous vitamin D was 18.94 (95% CI 11.47–31.25), p <0.001). The results were similar when vitamin D was examined as a categorical variable or divided into quintiles.
Conclusions
Prenatal vitamin D levels were low, and similar, among immigrant mothers of cases with selected developmental disorders and unaffected controls. This indicates that vitamin D unlikely mediates previously observed associations between maternal immigrant status and the selected developmental disorders in offspring. The proportion of immigrant mothers with severe vitamin D deficiency was very high, which underlines the importance of prenatal counselling and overall public health efforts to improve immigrant health.